Problems of development of monoprofile cities of Kazakhstan - Shedenov, U. K.; Myrzaliev, B. S. (Journal of Economic Research & Business Administration, 2015)
The problems of development of monoprofile cities of Kazakhstan are examined in the article, where almost 17% is concentrated urban population countries on that the network of rural resettlement is locked. The detailed analysis of branch orientation of monocities is thus conducted on current status of formative cities enterprises. Monoprofile cities mainly district centers are a bar in the decision of many problems of socio-economic development of both municipal and rural territories. The their dispersed allows to carry out a management vast territory, to decide the socio-economic tasks of development in a whole region. Monofunctional structure of economy, orientation in the past of formative cities enterprises on regional and central the markets of sale defined large dependence of small cities on vibrations in a leading production. A decline or complete absence of government order led and to falling of production volumes, social tension(height of unemployment the indexes of that in ten of one times exceed the indexes of cities; decline of standard of living of population) increased.